2022
DOI: 10.1371/journal.pone.0271569
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital schistosomiasis prevalence and diagnostic performance of urine filtration and urinalysis reagent strip in schoolchildren, Ethiopia

Abstract: Background Urogenital schistosomiasis has been known to be endemic in several lowland areas of Ethiopia. It is caused by Schistosoma haematobium and causes considerable public health problems to schoolchildren. Ethiopia, after mapping the distribution of the disease (2013 to 2015), launched school-based mass deworming program to treat schoolchildren for schistosomiasis and soil-transmitted helminthiasis (STH) across the country since 2015. However, there is no recent information about the prevalence of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
6
10
0
Order By: Relevance
“…In sum, the agreement of the URS with the urine filtration method in detecting the presence and estimating the classes of the intensity of S. haematobium infection was substantial (percent agreement = 84.4 and 78.4, respectively). A similar previous study also reported a similar level of agreement (Kappa = 0.64) between the URS and urine filtration in detecting the presence of S. haematobium infection in children [ 9 ].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In sum, the agreement of the URS with the urine filtration method in detecting the presence and estimating the classes of the intensity of S. haematobium infection was substantial (percent agreement = 84.4 and 78.4, respectively). A similar previous study also reported a similar level of agreement (Kappa = 0.64) between the URS and urine filtration in detecting the presence of S. haematobium infection in children [ 9 ].…”
Section: Discussionsupporting
confidence: 64%
“…A review article that combined 74 studies (102,447 participants) also estimated a 75% sensitivity and 87% specificity for detecting hematuria using URS applying a urine filtration microscope as a reference [ 14 ]. Two studies conducted in the current study area reported a higher sensitivity (>89%) of URS in detecting S. haematobium infections [ 7 , 9 ]. The decrease in the sensitivity of the URS in identifying individuals infected with S. haematobium in the current study could be due to the low intensity of infections that may have a negligible impact on the amount of blood in the urine, ‘hematuria’.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations